HAEMOPARASITIC INFECTIONS: RISK FACTORS AND EFFECTS ON PACKED CELL VOLUME OF PREGNANT WOMEN IN SAMARU, ZARIA (HAEMOPARASITIC INFECTIONS IN PREGNANT WOMEN) (International conference on multidisciplinary science, 2024)
Pregnant women in Nigeria still suffer a great burden of Plasmodium falciparum and Trypanosoma brucei gambiense infections. However, malaria is one of the dominant diseases during pregnancy. These haemoparasites affect both maternal and  foetal health. Structured questionnaires on socio-demographic and risk factors of haemoparasitic infections were administered on  125 consented pregnant women between the ages of 16-45 years in Samaru, Zaria. Each participant's venous blood sample (2ml)  was collected and average packed cell volume (PCV) was determined. The samples were examined for haemoparasites on thin and  thick blood smears stained with Giemsa dye using oil immersion (100x) objective of the light microscope. Only two types of haemoparasites were detected: Plasmodium falciparum (47.2%) and Trypanosoma brucei gambiense (4.0%), with a co-infection of 0.8%. Plasmodium falciparum infections were found across all the age-groups, but the youngest of pregnant women within 16-20 years and 21-25 years were the most infected. Women in their first trimester of pregnancy were significantly most infected with P. falciparum  (P=0.047). Women without  formal  education  (75.0%)  as well  as  those  that were unemployed  (48.1%) had  more  haemoparasites.  Living  in  houses  surrounded  by  stagnant  water  and  involvement  in  unprotected  farming  were  risks  for haemoparasitic infections. The prevalence of anaemia among the pregnant women was 45.6%. The presence of P. falciparum was statistically related to low PCV of 21-30% which was indicative of anaemia (P=0.000). Also, among the women with low PCV,  there was higher occurrence of T. b. gambiense with a case of co-infection. Pregnant women should be encouraged to enroll for ante-natal checkup at early stage of pregnancy. Parasitological examination during the ante-natal visits should not be limited to malaria alone: other neglected tropical diseases should be checked for and treated adequately.